HUBUNGAN LINGKUNGAN KELUARGA DENGAN SIKAP TANGGUNG JAWAB SISWA MADRASAH IBTIDAIYAH - Khusnaini Hidayatul Arofah; Dina Nur Antika; Eva Dwiyanti Putri M (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The purpose of this study was to evaluate the relationship between family environment and the attitude of responsibility of third grade students at MI Ar Risalah Ngawi.  The technique used was quantitative, with a correlational research design.  The population of this study was all third grade students totaling ten people, who were selected using a total sample approach. The data collection tool is a questionnaire with ten statement questions on each variable and a four-point Likert scale. Preliminary tests were conducted using the Shapiro-Wilk normality test and the ANOVA linearity test. Hypothesis testing used the Pearson product moment correlation technique. The analysis results showed a correlation coefficient of r = 0.226 with p = 0.530. This finding indicates that there is no significant relationship between the family environment and students' sense of responsibility. The family environment only contributes 5.1% to variations in students' sense of responsibility, while the rest is influenced by other factors. This study suggests the need for further exploration of other factors that are more dominant in shaping students' sense of responsibility at the elementary school level.